Hubungan Kebiasaan Konsumsi Teh dan Pola Konsumsi Pangan Enhancer dengan Kadar Hemoglobin Pada Remaja Putri di SMPN 5 Kota Jambi - Puteri, Aulia Salsabila; Farmawati, Tina Yuli; Jeki, Andicha Gustra; Novitasari, Maryam (Jurnal Akademika Baiturrahim Jambi, 2025)
Anemia, particularly iron deficiency anemia, is a significant global health problem, with a high prevalence among adolescent girls. In Indonesia, the prevalence of anemia reaches 23.7%, and adolescent girls are among the most vulnerable groups due to menstruation and unhealthy diets. One risk factor is the habit of consuming tea, especially black tea, which contains tannins and can inhibit the absorption of non-heme iron. Conversely, consumption of iron-enhancing foods such as vitamin C and animal protein is known to increase iron absorption. This study aims to determine the relationship between tea consumption habits and consumption of iron-enhancing foods with hemoglobin levels in adolescent girls. This study used a quantitative design with a cross-sectional approach and was conducted in May 2025 at SMPN 5 Jambi City. A sample of 77 female students was randomly selected from a population of 358 people. Data were collected through the SQ-FFQ questionnaire and hemoglobin levels were measured using the Hbchecker tool. Data analysis was performed univariately and bivariately with the Chi-square test (α < 0.05). The results showed that 74% of respondents had a high tea consumption habit, and 54.5% had anemia. There was a significant relationship between tea consumption habits and hemoglobin levels (p = 0.000). However, no significant relationship was found between consumption patterns of iron-enhancing foods and hemoglobin levels (p > 0.05). In conclusion, tea drinking habits are associated with an increased risk of anemia, while consumption of iron-enhancing foods has not shown a significant effect